Cartilaginous extracellular matrix derived from decellularized chondrocyte sheets for the reconstruction of osteochondral defects in rabbits. (November 2018) - Wang, Zhifa; Li, Zhiye; Li, Zhijin; Wu, Buling; Liu, Yanpu; Wu, Wei
Graphical abstract: Abstract: Cartilaginous extracellular matrix (ECM) materials derived from decellularized native articular cartilage are widely used in cartilage regeneration. However, it is difficult for endogenous cells to migrate into ECM derived from native cartilage owing to its nonporous structure and dense nature. Moreover, current decellularization approaches frequently lead to architectural breakdown and potential loss of surface composition of ECM. To solve this problem, we aimed to establish a novel biological ECM scaffold from chondrocyte sheets for cartilage regeneration. We cultured chondrocytes harvested from the auricular cartilage of 4-week-old New Zealand rabbits and enabled them to form cell sheets. These sheets were decellularized using sodium dodecyl sulfate (SDS) with three different concentrations, namely, 1%, 5%, and 10%, followed by 1% Triton X-100 and deoxyribonuclease enzyme solution. In vitro microstructural examination and mechanical tests demonstrated that 1% SDS not only removed chondrocytes completely but also maintained the native architecture and composition of ECM, thus avoiding the use of high-concentration SDS. Application of decellularized chondrocyte sheets for osteochondral defects in rabbits resulted in substantial host remodeling and variant regeneration of osteochondral tissues. One percent SDS-treated decellularized chondrocyte sheets contributed to the superior reconstruction of osteochondral defects as compared with 5% and 10% SDS groups, which includes vascularized subchondral bone, articular cartilage with adequate thickness, and integration with host tissues. Furthermore, ECM from 1% SDS significantly increased the migrating potential of bone marrow mesenchymal stem cells (BMSCs) in vitro . RT-PCR and western blot also revealed that ECM increased the expression of SOX-9 in BMSCs, whereas it decreased COL-X expression. In conclusion, our results suggested that the chondrocyte sheets decellularized with 1% SDS preserved the integrity and bioactivity, which favored cell recruitment and enabled osteochondral regeneration in the knee joints of rabbits, thus offering a promising approach for articular cartilage reconstruction without cell transplantation. Statement of Significance: Although biological extracellular matrix (ECM) derived from decellularized native cartilage has been widely used in cartilage regeneration, it is difficult for endogenous cells to migrate into ECM owing to its dense nature. Moreover, current decellularization approaches lead to architectural breakdown of ECM. This study established a novel biological ECM from decellularized chondrocyte sheets for cartilage regeneration. Our results suggested that cartilaginous ECM favored cell recruitment and enabled osteochondral regeneration in rabbits, thus offering a promising approach for articular cartilage reconstruction without cell transplantation. SDS 1% adequately decellularized the chondrocytes in cell sheets, whereas it maintained the native architecture and composition of ECM, thereby avoiding the use of high-concentration SDS and providing a new way to acquire cartilaginous ECM.